Effects of light pollution on inhabitants: Singapore's perspective - Chew, Loh Seng (Nanyang Technological University, 2022)
The most light-polluted country in the world is Singapore, and light pollution was found to be linked to a myriad of health problems that could lead to worsening living standards. Those affected may suffer from a range of tangible and intangible adverse effects, as a result, ranging from a drop in quality of living as well as physical and mental health conditions. Left untreated, this might lead to catastrophic outcomes. Plants and animals are not spared by light pollution as well, causing undesired ecological descent.